Floating knee fractures: patterns, treatment strategies and outcomes of 30 patients - Shinde, Abhishek T.; Oberai, Tanishque S.; Sastry, Subrahmanya V.; Perkar, Suryakant R.; Gadekar, Girish N.; Joshi, Ashwin M. (International Journal of Research in Orthopaedics, 2026)
Background: The “floating knee,” described by Blake and McBryde in 1975, involves ipsilateral femur and tibia fractures, usually from high-energy trauma like RTAs or falls. Common in young males, presenting with polytrauma and severe soft tissue damage. Management is complex, requiring early surgical fixation and intensive rehabilitation. Classification systems like Fraser’s help guide treatment and predict complications, including vascular, neurological, and ligament injuries. Methods: This retrospective study was conducted at a tertiary care hospital from March 2024-25, including 30 patients with surgically treated floating knee injuries. Fractures were classified using the Fraser system. Fixation methods and anaesthesia were selected based on clinical indications. Patients were followed up at 6 weeks, 6 months, 1 year. Data on demographics, surgical details, and functional outcomes were collected and analysed. Results: Analysis of 30 floating knee injury cases revealed that most patients were young males (76.7%), commonly aged 20-39 years, and predominantly injured in road traffic accidents (RTAs) (66.7%). Pain (80%) and swelling (63.3%) were the most frequent symptoms. Fraser type I fractures (50%) and closed injuries (76.7%) were most common. Spinal anaesthesia (56.7%) and intramedullary nailing (56.7%) were the preferred surgical approaches. Outcomes were excellent in 30% and good in 20%, though 50% experienced some complications, including delayed union, stiffness, or persistent limp. Conclusions: Floating knee injuries predominantly affect young males involved in high-energy trauma. Intramedullary nailing under spinal anaesthesia offers favourable outcomes with early mobilization and reduced morbidity. Despite good recovery in many cases, complications like stiffness and delayed union persist, underscoring the need for precise surgical technique, timely intervention, and comprehensive rehabilitation support.